Meningococcal Antigen Typing System Development and Application to the Evaluation of Effectiveness of Meningococcal B Vaccine and Possible Use for Other Purposes - Alexander Domnich; Roberto Gasparini; Daniela Amicizia; Giuseppe Boccadifuoco; Marzia Monica Giuliani; Donatella Panatto (Journal of Immunology Research)
Development of the 4-component meningococcal serogroup B vaccine (4CMenB) has required new assays for the reliable evaluation of the expression and cross-reactivity of those specific antigen variants that are predicted to be targeted by bactericidal antibodies elicited by the vaccine in different isolates. Existing laboratory techniques, such as multilocus sequence typing, are poorly suited to this purpose, since they do not provide information on the contribution of single vaccine components and therefore cannot be applied to estimate the potential coverage of the multicomponent vaccine. The hSBA, the only correlate of protection against invasive meningococcal disease accepted thus far, cannot conveniently be used to test large number of strains. To overcome these issues, the meningococcal antigen typing system (MATS) has been specifically developed in order to predict 4CMenB coverage of individual meningococcus serogroup B strains. To date, MATS has proved advantageous for several reasons, including its ability to assess both qualitative and quantitative aspects of surface antigens of single strains in a highly reproducible, rapid, and resource-saving manner, while its shortcomings include a possible underestimation of 4CMenB coverage and the use of pooled sera to calculate the positive bactericidal threshold. This paper provides an overview of MATS development and its field application.